Yorùbá Values and the Environment - John Ayọtunde Iṣọla Bẹwaji (Yoruba Studies Review, 2021)
This essay deploys Yorùbá ontology, epistemology and axiology to construct a Yorùbá ecological philosophy, or ecosophy. It argues that in contrast with the Judeo-Christian tradition of environmental anthropomorphic domination as the destiny of humanity or American pragmatism which encourages no stable traditions of values but what conduces to desired ends, the Yorùbá value system is by far more advanced in being more eco-respecting, eco-friendly and geared toward sustainable human habitation in a world in which he/she constitutes one small fraction of sentience. The essay developed around the responses to the following questions: a) What are values? b) How are values derived? c) Are there Yorùbá values? d) What is the environment? e) How are concepts of the environment derived? f) What is the relationship between values and the environment? g) What is the relationship between Yorùbá values and the environment? h) What are the inferences these have for one-health approach to the environment and sustainable human global co-existence?